Stocks of organic carbon in German agricultural soils—Key results of the first comprehensive inventory. Issue 6 (24th September 2020) - Poeplau, Christopher; Jacobs, Anna; Don, Axel; Vos, Cora; Schneider, Florian; Wittnebel, Mareille; Tiemeyer, Bärbel; Heidkamp, Arne; Prietz, Roland; Flessa, Heinz
Abstract: Background: There is considerable uncertainty about the actual size of the global soil organic carbon (SOC) pool and its spatial distribution due to insufficient and heterogeneous data coverage. Aims: We aimed to assess the size of the German agricultural SOC stock and develop a stratification approach that could be used in national greenhouse gas reporting. Methods: Soils from a total of 3104 sites, comprising 2234 croplands, 820 permanent grasslands and 50 sites with permanent crops (vineyards, orchards) were sampled in a grid of 8 × 8 km to a depth of 100 cm in fixed depth increments. In addition, a decade of management data was recorded in a questionnaire completed by farmers. Two different approaches were used to stratify cropland and grassland mineral soils and derive homogeneous groups: stratification via soil type (pedogenesis) and via SOC‐relevant soil properties. Results: A total of 146 soils were identified as organic soils, which stored by far the highest average SOC stock of 528 ± 201 Mg ha −1 in 0–100 cm depth. Of the mineral soils, croplands and permanent crops stored on average 61 ± 25 and 62 ± 25 Mg ha −1 in 0–30 cm (topsoil) and 35 ± 30 and 44 ± 28 Mg ha −1 in 30–100 cm (subsoil), while permanent grasslands stored significantly more SOC (88 ± 32 and 47 ± 50 Mg ha −1 in topsoil and subsoil). Overall, topsoils stored 67 ± 14% and subsoils 33 ± 14% of total SOC stocks. Soil C:N ratio, clay content and groundwater level were major factors that explained the spatial variability of SOC stocks in mineral soils. Accordingly, Podzols, Gleysols and Vertisols were found to have the highest SOC stocks. Conclusions: Stratification via soil properties yielded the most comparable cropland and grassland strata and is thus preferable for estimating land‐use change effects, e.g ., for greenhouse gas inventories. In total, 2.5 Pg C are stored in the upper 100 cm of German agricultural soils, making them the largest organic carbon pool in terrestrial ecosystems of Germany. This bares a large responsibility for the agricultural sector and society as a whole to maintain and, if possible, enhance this pool.